1996
DOI: 10.1007/bf02251064
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and self-esteem in working and nonworking persons with mental illness

Abstract: The purposes of this research were to examine first the relationship between work status and quality of life and self-esteem in persons with severe, persistent mental illness and secondly, the relationship between (a) demographic characteristics, attitudes toward psychotropic medications, and perceptions of the meaning of work and (b) quality of life and self-esteem in working and nonworking persons with severe mental illness. The sample included 92 persons (51 workers and 41 nonworkers). Instruments included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
90
2
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(108 citation statements)
references
References 21 publications
(27 reference statements)
8
90
2
8
Order By: Relevance
“…(19,21) Studies of people with mental illness have indicated that even low levels of work can have clinical benefits and contribute to improved overall mental health. (17,18,20) Similarly, other studies found that employment was associated with greater quality of life for people with physical disabilities and intellectual disabilities. (22,23) Yet, people with disabilities have historically been served by state and federal programs that require them to remain poor, and therefore unemployed, in order to get the health care services they need.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…(19,21) Studies of people with mental illness have indicated that even low levels of work can have clinical benefits and contribute to improved overall mental health. (17,18,20) Similarly, other studies found that employment was associated with greater quality of life for people with physical disabilities and intellectual disabilities. (22,23) Yet, people with disabilities have historically been served by state and federal programs that require them to remain poor, and therefore unemployed, in order to get the health care services they need.…”
Section: Introductionmentioning
confidence: 82%
“…A few small studies have investigated the effect of paid employment on quality of life, self-esteem and mental health among people with severe mental illness. (17,18,19,20) All but one of these studies found significant improvements in these domains for workers compared to non-workers with the same conditions. Further, studies of vocational rehabilitation (VR) outcomes have shown people with mental illness who obtain employment through VR also have higher levels of self-esteem and fewer symptoms than those who do not work.…”
Section: Introductionmentioning
confidence: 98%
“…This involves not only individual financial losses, but also individual suffering and family emotional and financial burden, as well as societal load, since absenteeism and presenteeism heavily impact employers and social welfare systems 6,8,9,11,16,21,29,30,31,32 . Regarding use of health services, the early detection and adequate treatment are important steps to reduce the impact and burden of mental disorders in general, and specifically related to employment status, they may be strong determinants of returning to the workforce 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the research achievements suggest that a lack of appropriate mental health is undoubtedly one of the justified factors in the unemployment. On the other hand, the employed people who suffer from psychological disorders to some extent have more self-esteem than the unemployed people who have the same psychological problems (17).…”
Section: Introductionmentioning
confidence: 99%